'A salutary lesson': male nurses and the Nursing and Midwifery Council - Mathers, Benjamin Jacob (2019)
This thesis is the first sociological examination of sex-based differences in referral and outcome for nurses that are subject to Nursing and Midwifery Council (NMC) Fitness-to-Practise (FtP) hearings. Despite male nurses only accounting for 10.8% of the nursing population in 2017, they also accounted for 23.8% of all those referred to the NMC over concerns about their conduct and 36.6% of all those struck-off as a result (NMC, 2017b). To date there has only been a limited number of sociological studies that have analysed the regulation of healthcare professionals in the UK (Currie et al., 2018). This research therefore helps fills a gap in the current sociological literature concerning both male nurses and the way that nurses are regulated in the UK.